Treasury Single Account (TSA) and cost of governance: Survey of MDAs in Anambra State - Okeke, Nnamdi Lawrence; Ezeala, George; Okoye, Nonso John; Egbunike, Chinedu Francis (Journal of Governance and Accountability Studies, 2023)
Purpose: This study examines the effect of TSA on Nigeria’s public sector governance cost. Research methodology: This study employed a descriptive survey research design. Ten Federal Ministries, Departments & Agencies (MDAs) in Anambra State constituted the study population. The study chose Ten respondents from each MDA were selected using purposive sampling. This study employed primary data from a structured questionnaire for data collection. Results: The results show that e-accounting and TSA have a substantial impact on national spending by curbing leakages, but with little effect on federally generated revenue. Thus, e-accounting and TSA significantly impact the cost of governance. Limitations: The study relied only on questionnaire responses, which is the perception of public-sector employees in MDAs. Contributions: This study contributes to governance and policy research by identifying the benefits of TSA in reducing the overall cost of governance. Novelty: By integrating all government accounts, enabling the government to track and monitor its activities at any time, and giving the government a comprehensive view of its financial position, this study supports stakeholder theory, in addition to the Public Finance Management Perspective, which maintains that the government should effectively manage all financial resources (mobilization and expenditure) for the benefit of the population.